Konstruksi Makna Tembok Ratapan Solo Sebagai Simbol Kritik Politik:Analisis Wacana Kritis Di Ruang Publik Digital - Muhammad Sowi Alhijry; Mutia Amdhani; Lusiano D.C. Gomes (Jurnal Common, 2026)
This study examines how the symbol “Tembok Ratapan Solo” (Solo Wailing Wall) was constructed and given meaning as a form of political satire and criticism within the digital public sphere. It addresses three interrelated questions: how the symbol’s meaning is constructed at the textual level through diction, metaphor, and layers of denotation, connotation, and myth; how discursive practice produces, distributes, and consumes the discourse across platforms; and how the discourse reflects the sociocultural contest between hegemony and counter-hegemony in post-Jokowi Indonesian politics. Using a constructivist paradigm and a qualitative descriptive approach, the study employs Norman Fairclough’s three-dimensional Critical Discourse Analysis as its sole method. Within this framework, Barthes’ semiotics and Berger and Luckmann’s social construction serve as analytical tools for the textual dimension, Habermas’ public sphere for the discursive dimension, and Gramsci’s hegemony for the sociocultural dimension. The renaming of former President Joko Widodo’s residence on Google Maps, amplified through Instagram, TikTok, and mainstream media, transformed a private home into a contested political symbol. The findings show that the symbol functions as grassroots criticism of political dynasties and the continuity of Jokowi’s post-presidential influence, conveyed largely through connotation and the intertextual borrowing of a global religious symbol. The study’s central contribution is its identification of a paradoxical logic: contemporary Indonesian digital satire is among the most effective expressions of grassroots critique, yet also the most vulnerable to commodification and re-appropriation by the very power it criticizes, as indicated by reports of an orchestrated “Wailing Wall tourism.” Keywords: political satire, critical discourse analysis, digital public sphere, political symbol, hegemony.